'Flying High in a Plane' Appellate Body Report, European Communities and Certain Member States – Measures Affecting Trade in Large Civil Aircraft. Issue 2 (7th April 2020) - Crivelli, Pramila; Rubini, Luca
Abstract: This article reviews the Appellate Body decision in the implementation phase of the EC–Aircraft dispute. Focusing on some of the key findings, we assess whether they are legally and economically correct. We conclude that (a) though still unclear, the test for establishing de facto contingency on import substitution subsidies is probably too demanding; (b) though legitimate, the interpretation of the remedy of removal of the adverse effects for actionable subsidies is the weakest and most deferential possible; (c) the hesitation in confirming that quantitative methods are the key tool to define the relevant market is unwelcome; and (d) the Appellate Body correctly recognize the importance for Panels to consider, in the context of the serious prejudice analysis, whether the like product of the complainant has been subsidized. Most importantly, the analysis of this case, set within the broader jurisprudence and practice, has led us to conclude that WTO subsidy disciplines are not particularly strong. The review of the main economic theories justifying subsidy control (strategic trade policy, terms of trade, private information, commitment theory) has shown that no single theory is able to fully account for subsidies and the need to control them. The key question is the definition of what we want to achieve by controlling subsidies, which is the main message sent to the policy-makers and negotiators that are currently considering law reform.